Migratory Insertion Strategies for Dearomatization - Zeidan, Nicolas; Lautens, Mark (Synthesis, 2019)
Development of strategies for molecule functionalization by dearomatization has surged in the last two decades. The benefits of overcoming the resonance stabilization energy outweigh the cost; diverse compounds could be accessed in a short number of steps. One approach that has been of interest in recent years is the dearomatization of indoles and other (hetero)aromatic compounds by migratory insertion. The chiral σ-bond palladium intermediate could be reduced or trapped by a second functionalization. In this short review we will summarize the recently discovered reactions from our group and others in this field of metal-catalyzed dearomatizations by migratory insertion.1 Introduction2 Monofunctionalizations: Heck and Reductive Heck Reactions2.1 N-Tethered Heterocycles2.2 Non-N-tethered Heterocycles2.3 Non-heterocycles3 Dearomative Difunctionalizations: Interrupted Heck Reaction3.1 N-Tethered Heterocycles3.2 Non-N-tethered Heterocycles4 Conclusion
Keywords: palladium; nickel; dearomatization; migratory insertion; carbopalladation; difunctionalization